2016
DOI: 10.1038/onc.2015.494
|View full text |Cite
|
Sign up to set email alerts
|

SFRP2 augments WNT16B signaling to promote therapeutic resistance in the damaged tumor microenvironment

Abstract: Most tumors initially respond to cytotoxic treatments, but acquired resistance often follows. The tumor microenvironment (TME) is a major barrier to clinical success by compromising therapeutic efficacy, and pathological relevance of multiple soluble factors released by a therapeutically remodeled TME remains largely unexplored. Here we show that the secreted frizzled-related protein 2 (SFRP2), a Wnt pathway modulator, is produced by human primary fibroblasts after genotoxic treatments. SFRP2 induction is rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 50 publications
4
75
0
Order By: Relevance
“…To clarify whether SFRP2 increases or decreases as tumors progress, we previously found that SFRP2 signal intensity increased as a function of tumor volume using SFRP2-targeted molecular imaging of a mouse tumor in vivo [33]. Other studies confirmed our observation showing that overexpression of SFRP2 increases angiogenesis and tumor growth in vitro and in vivo , [8,9,4,6,34,1,7,2,3]. Furthermore, antagonizing SFRP2 with a monoclonal antibody inhibits tumor growth in vivo [10], which establishes the preponderance of evidence that SFRP2 stimulates, rather than suppresses, tumor growth.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To clarify whether SFRP2 increases or decreases as tumors progress, we previously found that SFRP2 signal intensity increased as a function of tumor volume using SFRP2-targeted molecular imaging of a mouse tumor in vivo [33]. Other studies confirmed our observation showing that overexpression of SFRP2 increases angiogenesis and tumor growth in vitro and in vivo , [8,9,4,6,34,1,7,2,3]. Furthermore, antagonizing SFRP2 with a monoclonal antibody inhibits tumor growth in vivo [10], which establishes the preponderance of evidence that SFRP2 stimulates, rather than suppresses, tumor growth.…”
Section: Discussionsupporting
confidence: 79%
“…Overexpression of transfected SFRP2 in MCF7 breast adenocarcinoma cells increased their resistance to apoptotic signals in vitro [6]. Likewise, SFRP2 is a key factor in chemotherapy resistance of damaged tumor microenvironment [7]. …”
Section: Introductionmentioning
confidence: 99%
“…However, overexpression of sFRP2 has been reported in renal cancer [8], human angiosarcoma, and breast cancer [21, 22], which leads to angiogenesis stimulation by activation of the calcineurin/NFATc3 pathway. Furthermore, recently enhanced sFRP2 expression has been associated with promoting therapeutic resistance and metastatic potential within solid tumors by specifically altering the tumor microenvironment [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent data demonstrated that HGF is a critical TME determinant of resistance to BRAF inhibitors, setting the baseline for combinations of HGF-targeting monoclonal antibodies and RTK inhibitors that dampen the receptor c-Met activation [78,79]. Identification of the distinct role of stromaderived WNT16B in prostate cancer strongly supports translational studies in cancer therapy, as evidenced by the pilot preclinical trial integrating a monoclonal WNT16B antibody and routine chemotherapy to treat prostate tumors [73]. It is tempting to compare the efficacy of WNT16B-implicated pathway blockade and a wider suppression of the TME response to genotoxicity by inactivating the NF-κB complex.…”
Section: Development Of Targeting Strategies In Precision Medicinementioning
confidence: 69%
“…Expression of the secreted frizzled-related protein 2 (SFRP2), a typical modulator of Wnt signaling, is increased in the stroma damaged by the chemotherapeutic cycles [56]. Beyond holding the potential to promote angiogenesis via the calcineurin/NFAT signaling in a noncanonical Wnt pathway [71,72], SFRP2 can interact directly with WNT16B to enhance its canonical activities, eventually generating a substantially strengthened malignant phenotype including remarkable drug resistance in prostate cancer [73]. Data from targeting angiopoietins (Ang1, Ang2, Ang4) which cause CAF accumulation and neoangiogenesis in the TME, and TEK (referring to Tie1/Tie2) receptors responsible for the maturation and plasticity of blood vessels, are recently reported [74,75].…”
Section: Patient Centered Medicine 82mentioning
confidence: 99%